2018
DOI: 10.1136/annrheumdis-2017-212535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnancy on disease flares in patients with systemic lupus erythematosus

Abstract: Our study supports and extends previous findings that the incidence of flare is increased during pregnancy and within the 3 months postpartum. Continuing HCQ, however, appeared to mitigate the risk of flare during and after pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 27 publications
4
117
2
3
Order By: Relevance
“…Studies of disease exacerbation or ares in pregnant SLE patients have been performed in several groups, and even among the case-controlled studies, have shown con icting results [4][5][6][7][8][9][10]21]. Details of patient characteristics and ares among previous case-controlled studies, as well as this study, are shown in Supplementary Table 2.…”
Section: Discussionmentioning
confidence: 93%
“…Studies of disease exacerbation or ares in pregnant SLE patients have been performed in several groups, and even among the case-controlled studies, have shown con icting results [4][5][6][7][8][9][10]21]. Details of patient characteristics and ares among previous case-controlled studies, as well as this study, are shown in Supplementary Table 2.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies support maternal and pregnancy benefit of HCQ and low risk for mother and fetus . Potential contraindications include allergy, adverse side effects, or intolerance.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…We strongly recommend HCQ, azathioprine/6‐mercaptopurine, colchicine, and sulfasalazine, medications commonly used for RMD, as compatible for use throughout pregnancy ( ).…”
Section: Results/recommendationsmentioning
confidence: 99%
“…An important message to providers and patients is that many women with rheumatic diseases have successful pregnancies and healthy babies . Moreover, some women will choose to pursue pregnancy even if they face substantial health risks .…”
Section: Discussionmentioning
confidence: 99%